Students' Preferences for Varied Learning Methods: An Empirical Study of the Effectiveness and Appeal of Diverse Instructional Approaches - Siregar, Rahmat Sapaat (MANDAILING GLOBAL EDUKASIA, 2024)
This study focuses on analyzing students' preferences for the learning methods used by teachers, evaluating the effectiveness and attractiveness of each approach used instructionally. This study was conducted on junior high school students. This study used a descriptive quantitative approach, with a sample of 40 students from grades VII to IX, taken by stratified random sampling. Data collection was carried out through a structured questionnaire with a five-point Likert scale consisting of three components: preference method, effectiveness, and attractiveness. Data processing was carried out descriptively and inferentially statistically including simple linear regression analysis and ANOVA tests. Among the findings, recommendations were also submitted to teachers to add learning videos, and increase gamification activities, considering the economic and cultural backgrounds of students. In addition, conventional methods such as practicing questions and answering questions still have a fairly large population according to their method preferences. The results of this study indicate that students tend to choose more varied learning methods, this is to support the process of adapting and socializing students with the outside world, as well as increasing students' innovation and creativity.